Changing Phase of Industry form Generalization to Specification: A Study on Recent Innovation in the Field of Sports Shoe Segment - Sahai, Ashok Kumar; Goel, Anuj (Journal of Commerce and Trade, 2018)
Today People are very much conscious about their health and fitness and becoming sports freak. With the increase in population in urban areas people are becoming more health conscious due to which they prefer to join various clubs or sports meets in order to keep them fit. This leads to increase in demand of sports goods & accessories and out of which footwear is consider as one of the important product which is required in all the physical and sports related activities. If we talk about Indian companies approximately 80 percent of Indian sports shoe market is in the hands of four big global players namely ADIDAS, REEBOK, NIKE and PUMA.. All four global footwear giants are keep on producing sports shoes by identifying the attributes of games as well as the personality of players, because gone are the days when companies manufacture sports shoes as per the requirement of sports, now company primarily focus on the physical requirement of players and then they are focusing on requirement of the sports. In short we can say now these companies or brands moving from generalization concept of production/manufacturing to specification of product and its utility for the sports personals.